Aquatic Oligochaetes of Iraq's Southern Marshes - Baghdad Science Journal (مجلة بغداد للعلوم)
Aquatic Oligochaetes community in the Iraqi southern marshes, Al- Hawiezah, Al-Chibayish and Al-Hammar, have been studied for the period from July 2006 to June 2007. Two sites within each marsh, in addition to a reference site located at Shatt Al-Garma, have been chosen for sample collection using Ekman dredge. The results revealed that the highest average annual density was 16800 individual / m2 recorded in Al-Hawiezah marsh, while in Al-Chibayish and al-Hammar marsh the density did not exceed 5111 individual/m2. In contrast, the density of Oligochaetes recorded in Shatt Al-Garma was about 10500 individual / m2. The highest monthly density was recorded in April 2007.The highest local percentage occurrence was 96% recorded in Al-Hawiezah marsh, while the highest average monthly percentage occurrence was recorded in January 2007.The study revealed the presence of 19 Oligochaetes species belonging to 14 genera and 4 families. Naididae was represented by 8 spp.; Tubuficidae 8 spp.; Lumbriculidae 2 spp. and Lumbricidae 1 spp. Tubificid worms formed about 73% of the total count while Naididae formed 15%, Lumbriculidae 8% and Lumbricidae 4%.Among Tubificidae, Limnodrilus was the most abundant genus composed about 35% of L. hoffmeisteri; 11.5% L. claparedianus; 8% L. profundicola and 4.7% L. maumeensis, followed by Tubifex tubifex 23%. Other species were Branchuira sowerbyi formed 15%; 2.8 and 2 % for Peloscolex velutinus and Aulodrilus pigueti respectively. Naididae worms comprised 8 species including 32% of Dero digitata, 24% of Nais variabilis, 14% of Amphichaeta sp. and 11% of each of D.obtuse and Pristina longiseta. However, D. dorsalis represented only 7.5% of the total Naididae. Few individuals of B. sowerbyi and Lumbriculus variegates, with two regenerated parts at the posterior end were also detected in some samples. This case was considered a rare observation within the population of these worms in this particular area.